Exploring the characteristics of violent video game players - Phillips, R.S. (2018)
The role of violent video games (VVG) in increasing levels of aggression in players is a topic that has been debated for decades. While a simple cause and effect relationship is not present, it is apparent from the literature that VVGs do have a relationship with elevated levels of aggression within some players. The first chapter of this Thesis presents a systematic review of the literature focusing on additional factors included in the research to explain this finding. However, a lack of standardisation in both measurement and reporting of results making interpretation difficult. The second chapter provides a critique of the non-experimental methods used within video game (VG) research. The third chapter focuses on a non-experimental study which highlighted the differences in aggression, motivations for playing, empathy, and personality in a group of VVG players. The final chapter presents the results of a service evaluation of the management of VGs within a high secure psychiatric hospital, which highlighted the real-world implication of an unclear literature base. The conclusions of this thesis highlight the variation in the quality of the literature available and stresses the need to conduct research with targeted populations, both VG players and clinically populations, to fully understand the relationship between engaging in VVG and increased aggression.